Watch Out for a Second SNP: Focus on Multi-Nucleotide Variants in Coding Regions and Rescued Stop-Gained - Degalez, Fabien; Jehl, Frédéric; Muret, Kévin; Bernard, Maria; Lecerf, Frédéric; Lagoutte, Laetitia; Désert, Colette; Pitel, Frédérique; Klopp, Christophe; Lagarrigue, Sandrine (Frontiers in Genetics, 2021)
Most Single Nucleotide Polymorphisms (SNPs) are located in non-coding regions but the fraction usually studied is harbored in protein-coding regions because potential impacts on proteins are relatively easy to predict by popular tools such as Variant Effect Predictor. These tools annotate variants independently without considering the potential effect of grouped or haplotypic variations, often called “Multi-Nucleotide Variants” (MNVs). Here we used a large RNA-seq dataset to survey MNVs, comprising 382 chicken samples originating from 11 populations analyzed in the companion paper in which 9.5M SNPs - including 3.3M SNPs with reliable genotypes - were detected. We focused our study on in-codon MNVs and evaluate their potential mis-annotation. Using GATK haplotypeCaller read-based phasing results, we identified 2,965 MNVs observed in at least 5 individuals located in 1,792 genes. We found 41.1% of them showing a novel impact when compared to the effect of their constituent SNPs analyzed separately. The biggest impact variation flux concerns the originally annotated stop-gained consequences, for which around 95% were rescued; this flux is followed by the missense consequences for which 37% were re-annotated with a different amino acid. We then present in more depth the rescued stop-gained MNVs and give an illustration in the SLC27A4 gene. As previously shown in human datasets, our results in chicken demonstrate the value of haplotype-aware variant annotation, and the interest to consider MNVs in coding region particularly when searching severe functional consequence such as stop-gained variant.